PSIKOLOGI PENDIDIKAN DALAM INKLUSI SISWA BERKEBUTUHAN KHUSUS DI ERA DIGITAL: STUDI LITERATUR TENTANG MEMBANGUN LINGKUNGAN BELAJAR YANG RESPONSIF - Archristhea Amahoru; Loso Judijanto; Muhammad Sukron Fauzi; Dwi Hadita Ayu; Rosyida Nurul Anwar (Ekasakti Jurnal Penelitian dan Pengabdian, 2024)
This research aims to provide in-depth insight into how educational psychology can support the inclusion of students with special needs in the digital era. By exploring existing literature, it is hoped that strategies and tools can be found that can create a responsive learning environment. The importance of literature study in research, especially to develop a solid theoretical framework. Through literature reviews, researchers not only understand existing concepts and theories, but can also identify gaps in previous research, providing an opportunity to build a strong foundation. The results of this research emphasize the importance of a differentiated approach in teaching to create an inclusive and responsive learning environment, where educators can consider students' individual needs and abilities by adapting teaching methods through strategies such as collaborative learning and the use of multimedia. Information and communications technology (ICT) also plays a crucial role, enabling material adjustments and real-time feedback that enrich the learning experience of students, including those with special needs. In addition, building a supportive social environment, through positive interactions and emotional support from educators, is essential to encourage students' self-confidence and active participation. A continuous evaluation process and feedback from students helps educators understand individual needs and preferences, creating a comfortable atmosphere for sharing ideas and reflection. Overall, the combination of a differentiation approach, use of technology, and an inclusive social environment can improve academic learning outcomes as well as students' social and emotional development.